Nanog1 in NTERA-2 and recombinant NanogP8 from somatic cancer cells adopt multiple protein conformations and migrate at multiple M.W species. - Bigang Liu; Mark D Badeaux; Grace Choy; Dhyan Chandra; Irvin Shen; Collene R Jeter; Kiera Rycaj; Chia-Fang Lee; Maria D Person; Can Liu; Yueping Chen; Jianjun Shen; et al. (PLoS ONE)
Human Nanog1 is a 305-amino acid (aa) homeodomain-containing transcription factor critical for the pluripotency of embryonic stem (ES) and embryonal carcinoma (EC) cells. Somatic cancer cells predominantly express a retrogene homolog of Nanog1 called NanogP8, which is ~99% similar to Nanog at the aa level. Although the predicted M.W of Nanog1/NanogP8 is ∼35 kD, both have been reported to migrate, on Western blotting (WB), at apparent molecular masses of 29-80 kD. Whether all these reported protein bands represent authentic Nanog proteins is unclear. Furthermore, detailed biochemical studies on Nanog1/NanogpP8 have been lacking. By combining WB using 8 anti-Nanog1 antibodies, immunoprecipitation, mass spectrometry, and studies using recombinant proteins, here we provide direct evidence that the Nanog1 protein in NTERA-2 EC cells exists as multiple M.W species from ~22 kD to 100 kD with a major 42 kD band detectable on WB. We then demonstrate that recombinant NanogP8 (rNanogP8) proteins made in bacteria using cDNAs from multiple cancer cells also migrate, on denaturing SDS-PAGE, at ~28 kD to 180 kD. Interestingly, different anti-Nanog1 antibodies exhibit differential reactivity towards rNanogP8 proteins, which can spontaneously form high M.W protein species. Finally, we show that most long-term cultured cancer cell lines seem to express very low levels of or different endogenous NanogP8 protein that cannot be readily detected by immunoprecipitation. Altogether, the current study reveals unique biochemical properties of Nanog1 in EC cells and NanogP8 in somatic cancer cells.